Analisis Struktur Modal Optimal Dengan Mempertimbangkan Financial Distress Cost dan Agency Cost(Studi Kasus: PT Perkebunan Nusantara IX) - Yulianto, Fitria, Dr. Syamsudin, M.M, Dra. Rina Trisnawati, M.Si, Ak, Ph.d (2017)
The purpose of this study is to determine the optimal capital structure in PT Perkebunan Nusantara IX in finding sources of financing operational and investment. The type of research used is case study, with quantitative descriptive method. Sources of data are taken from financial report. Technical analysis for finding the optimal capital structure using Modigliani-Miller II theory with agency cost and financial distress. The results of this study indicate that the highest corporate value in the proportion is 30% debt and 70% equity. Besides the value of the company, it should also be seen in terms of cost of capital. Weighted Average Cost of Capital (WACC) are lowest in the proportion of 40% debt and 60% equity. It can be concluded that the optimal capital structure in the proportion of debt 30% and 40%.